Place Attachment Kampung Kota Semarang Studi Kasus Kampung Batik Semarang Timur - Ceratomia Sonaesti; Edi Purwanto; Wijayanti Wijayanti (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
Kampung Batik Semarang is now developing into a tourist destination that is thought to have a place attachment. Place attachment is built through place creation, place identity and place dependence. This study uses a qualitative method, aims to identify places that contain place attachments, find out the processes and factors that form place attachments, and map the relationship patterns of these places. The results conclude that the creation of place attachments in physical elements, activities and functions, due to the development of latent activities. The identity of a place is built through its physical and non-physical identity. Place dependence is manifested in a sense of belonging, security, pride, memory, a feeling of being at home, and a desire to maintain a place. The factors that influence it are the fulfillment of the community's need for public space, historical, cultural and economic factors, good location, physical condition and available facilities.